Evaluation of cytotoxicity and anti-inflammatory action of AH-Plus sealer with and without petasin, pachymic acid, curcumin & shilajit: an invitro-study - Selvanathan M. J. Vinola; Sekar Mahalaxmi (Scientific Reports)
Abstract AH Plus, an epoxy resin-based sealer extensively employed in endodontics, is renowned for its excellent dimensional stability and effective adhesion to dentin. Nevertheless, extensive clinical research has documented its propensity to induce inflammation, especially when freshly mixed. Phytochemicals such as petasin, pachymic acid, curcumin, and shilajit are known for their anti-inflammatory and analgesic properties. This study aimed to investigate the influence of these phytochemicals on cytotoxicity and anti-inflammatory potential of AH Plus. Experimental groups included AH Plus-resin sealer (AHR) with and without 10% petasin (AHP), 0.75% pachymic acid (AHA), 0.5% curcumin (AHC) and 6% shilajit (AHS) at ratios of 5:1 and 10:1 respectively. Stem cells of apical papilla (SCAP) were exposed to the experimental sealers and assessed for cytotoxicity (MTT assay) and cytokine expression levels of IL-6, IL-8 and TNF-α (ELISA) at different time intervals (0 h, 24 h and 48 h). Experiments were performed in triplicate and analyzed using one-way ANOVA (p < 0.05). All experimental groups demonstrated varying levels of decreased cytotoxicity and cytokine expression compared to the control group; specifically in 5:1 ratio. Thus, it can be concluded that addition of petasin, pachymic acid, curcumin, and shilajit with AH Plus sealer in 5:1 ratio resulted in decreased cytotoxicity and enhanced anti-inflammatory properties.